(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
More than half of the global population currently lives in urbanised areas. Consequently, a significant vegetation cover is continuously cleared as cities grow. Where surface grounds are not covered by impermeable surfaces, open soil is eroded by runoff, putting several ecological systems at risk of degradation. This study aimed at investigating the problem of soil loss in Windhoek. High amounts of soil loss are found in very low income settlements compared to high income areas. More soil loss is also found on medium slopes despite the fact that many eroded features are on gentle slopes. Grass cover plays a major role in the magnitude of soil loss. These findings are expected to be of particular interest to land managers in their bid to reduce potential environmental degradation, and also city planners, while they attempt to integrate control measures into the city’s development. Any effort towards soil conservation would be highly significant, as the loss of topsoil is currently a great concern in the city.